KONTRIBUSI PENDAPATAN IBU RUMAH TANGGA TERHADAP PENDAPATAN KELUARGA (STUDI KASUS PENJUAL AKSESORIS DI KAWASAN BUKIT KASIH KANONANG) - Gloria Meriam Jenevi Lopulalang; Mex Frans Lodwyk Sondakh; Melsje Yellie Memah (AGRI-SOSIOEKONOMI, 2020)
This study aims to see how much the contribution of housewives who sell accessories to family income in the Bukit Kasih Kanonang area. This research was conducted from November 2019 to March 2020. The data used in this study are primary data and secondary data. Primary data were obtained from interviews with accessories selling respondents using a questionnaire, while secondary data were obtained from literature and previous research. The method of determining the sample is using purposive sampling method. Retrieval of respondent data, namely housewives who still have husbands, have dependents and who work more than 10 days a month. The results showed that The contribution of the accessories selling housewives' income to family income is 33.81% of the total family income. And if seen from the age of the most respondents are aged 41-46 years, if you look at the education level of the most respondents are at the junior high school education level, if you look at the number of dependents of the respondent, the largest number of dependents is the number of dependents 2, if you look at the length of work of the respondent then It can be seen that the most respondents' length of work is 1-5 years, if seen from the highest number of working days of respondents, namely 16 working days in a month and when viewed based on the husband's job, the highest contribution of housewives is work as a photographer, with a percentage of 65.51%.